2018
DOI: 10.1108/amhid-06-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behaviour therapy for low self-esteem in a person with a learning disability: a case study

Abstract: Purpose Low self-esteem is common in people with learning disabilities. There is limited research examining the effectiveness of cognitive behavioural therapy (CBT) focused on low self-esteem within this client group. The purpose of this paper is to add to the limited evidence by describing the use of CBT focused on low self-esteem for a person with a learning disability in the context of emotion regulation difficulties. Design/methodology/approach An individual case study design was used, with repeated quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The results also revealed that social work interventions using the CBT had a significant effect on all cognitive, behavioral, emotional, and motivational dimensions among adolescents with physical disability. This finding complies with the results of some studies such as Evans and Allze, Jansson et al and Hronis et al For example, Evans and Allze (2018) demonstrated that CBT decrease the client's feelings of anger and increase their self-esteem [26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…The results also revealed that social work interventions using the CBT had a significant effect on all cognitive, behavioral, emotional, and motivational dimensions among adolescents with physical disability. This finding complies with the results of some studies such as Evans and Allze, Jansson et al and Hronis et al For example, Evans and Allze (2018) demonstrated that CBT decrease the client's feelings of anger and increase their self-esteem [26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have examined the effectiveness of CBT [ 38 47 ]. In these studies, the researchers evaluated the primary outcomes include psychological wellbeing [ 43 – 47 ], depression symptom [ 45 , 46 , 48 ], mood and anxiety symptom [ 39 , 46 , 47 , 49 ], depression [ 38 , 47 , 49 ], self-stigma [ 46 ], quality of life [ 45 ], self-esteem [ 40 45 , 47 , 49 ], optimization, social support[ 43 ] and the secondary outcomes of CBT include self-esteem [ 48 ], automatic thoughts [ 38 ] in different samples; university student [ 43 ], obese females [ 42 ], physically disabled females [ 44 ], early psychosis patients [ 48 ], patients with depression [ 38 , 46 ], patients with bipolar disorder [ 39 ], psychiatric patients [ 50 ], patients with MDD [ 45 ], people with a learning disability [ 40 ]. In most of which indicated that CBT has improved self-esteem after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that Dialectical Behaviour Therapy adapted for people with intellectual disabilities can reduce self-harming and aggressive behaviours (Brown et al , 2013; McNair et al , 2017), as well overall psychological distress (Morrissey and Ingamells, 2011). Similarly, Cognitive Behaviour Therapy has increased self-esteem and reduced feelings of anger for people with intellectual disabilities (Evans and Allez, 2018), whilst also increasing adaptive emotion management skills (Ashworth et al , 2017). Whilst intervention studies for people with EUPD and intellectual disabilities is limited (Iversen et al , 2019), it is argued that mainstream literature regarding EUPD treatment is relevant to address the psychological and social needs of those with EUPD and an intellectual disability (Taylor and Morrissey, 2012).…”
Section: Introductionmentioning
confidence: 99%